The relationship between franchise and franchisor: A study of the Vietnamese retail franchising - Huong, Hoang Thi Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 27 No 1, 2011)
Abstract. Decades saw the fast growth and high success of franchising in global market but the very early stage of franchising in Vietnam market. Previous researches about franchising have considerably contributed to better understanding of relationships between franchisor and franchise. However, the franchisor-franchise relationship has yet to be fully explored, knowledge of the factors that produce a high quality relationship between franchisor and franchise are critical to the advancement of knowledge in the retail industry. Leader-Member Exchange (LMX) theory is offered of an effective theoretical model of antecedents that can predict the effectiveness the franchisor-franchise relationship. The model proposed has been tested with 500 franchises operating in the retail (fashion, food and beverage) in the Vietnamese franchised distribution system. The results of this study generally support the hypothesized model and strongly support for the idea that the quality of the relationship will lead to higher level of franchise’s job satisfaction, performance business, trust and commitment. This study also confirms the importance of the franchisor’s support and mediating role of trust and commitment to the success of franchising relationship. Finally, this study provides franchisors with valuable information for establishing an effective management to improve the relationship between franchisor and franchise and thus improves the rate of success of both franchise and franchisor.